Effect of servers' arrangement on the performance of a loop thermosyphon system used in data center. (25th June 2021) - Zou, Sikai; Zhang, Quan; Yue, Chang; Du, Sheng
Highlights: A loop thermosyphon system was studied under four typical servers' arrangements. The servers' arrangement had little influence on the steady-state operating performance. Clumped the servers at the bottom of the rack can shorten the start-up time under low rack utilization. Abstract: In applications, servers' arrangements are often chaotic owing to a lack of regulation, which may affect the performance of loop thermosyphon systems. In this study, the optimal filling ratio, thermal resistance and operating performance of a loop thermosyphon system were experimentally investigated under four typical servers' arrangements. Compared with other servers' arrangements, the optimal filling ratio range changed from 30.3–37.3% to 28.0–35.0% when clumped the servers at the bottom of the rack. However, the system thermal resistances were approximately equal (0.0034–0.0036 °C/W) at optimal filling ratios under the four servers' arrangements, indicating that a filling ratio within 30.3–35.0% was suitable for all servers' arrangements. At 32.7% filling ratio, the operating performances under different servers' arrangements and heating powers were compared and analyzed. Although the maximum difference in the evaporator inlet air temperatures exceeded 10 °C, the servers' arrangement did not affect the steady-state operating performance. Moreover, the servers' arrangement had little influence on start-up times under 4 kW and 6 kW heating powers but had a significant influence under 2 kW heating power. Clumped the servers at the bottom of the rack can shorten the start-up time under low rack utilization (2 kW heating power).